Persepsi Pengemudi-Pengemudi Bus Ekspres Di Utara Semenanjung Malaysia Terhadap Kepatuhan Dan Partisipasi Keamanan - Munauwar Mustafa; Mohd Azril Ismail; Ummey Abdul Razak; Donny Abdul Latief Poespowidjojo (UIR Press, 2016)
This research was carried out to determine express bus drivers’ perceptions towards safety participation and safety compliance, which are two dimensions of a variable known as safety performance. Population of the study consisted of 372 express bus drivers from 15 companies operating in the north of Peninsular Malaysia. By using simple random sampling, 200 survey forms were distributed. However, only 103 forms were returned and deemed usable for data analysis. Mean score for overall safety performance is 4.09. Mean score for safety compliance at 4.15 is a little bit higher than that of safety participation at 4.04. High mean score for safety performance showed that express bus drivers are very concerned about safety at workplace in terms of their participation and compliance of safety-related activities organized by their companies. In other words, express bus drivers did have the willingness to go for safety in a normal situation and they might not be the culprit in intentionally causing an accident. Hence, further studies should be carried out to determine other factors that might contribute to accidents involving express busses with the intention to prevent accidents from happening in the future.